Pengaruh Biaya Operasional Pada Laba Bersih Yang Dihasilkan: Systematic Literature Review - Lorence Manalu; Masduki Asbari; W Winanti (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to explore the relationship between operating costs and net profit generated by companies. In the context of increasing competition, it is important for companies to understand how the management of operating costs can affect their financial performance. The method used in this research is a systematic literature review, in which the authors collect and analyze relevant articles from various sources, including Google Scholar. The results of this study are expected to provide useful insights for company management in strategic decision-making, as well as contribute to the development of further research in this area. By understanding the influence of operating costs, companies can formulate more effective strategies to increase the company's net profit.